Prevalence of caries on permanent first molar on cerebral palsy children aged 6-12 years old in SLB Bandung at 2010 - Rizkyawati, Devy; Gartika, Meirina; Runkat, Jakobus (Faculty of Dentistry Universitas Padjadjaran, 2010)
Introduction: Caries is an irreversible tooth disease that is frequently encountered in the community. Caries on the permanent first molar, if not being treated, can cause tooth loss and other disadvantages. Cerebral palsy children have a motor abnormalities, that leads to high prevalence of caries. The purpose of this research was to find the prevalence of caries on the first permanent molar teeth in cerebral palsy children ages 6-12 years old. Methods: Type of research was descriptive research. Population is the cerebral palsy children in SLB Bandung, with criterion of children aged 6-12 years, has four permanent first molars, and no patches or restorations on permanent first molars. Samples from the population was taken by total sampling, a total of 26 cerebral palsy children. Results: The result shown that 22 cerebral palsy children (84.62%) tends caries on their first permanent molar teeth. The prevalence of caries on the first permanent molar tooth of the maxilla of children with cerebral palsy is 76.92 % and on the first permanent molar of the mandible is 78.84%. Conclusion: Prevalence of caries on the first permanent molar teeth in cerebral palsy children ages 6-12 years old is high.